Remote sensing of the sea oil pollution by means of high frequency surface scattering - POGORZELSKI, S. J. (Archives of Acoustics, 2014)
The statistical properties of the ultrasonic signal scattered at a rough surface of both clean water and water covered with a layer of oil substance in an outdoor pond were examined. The results obtained by means of free-floating acoustic buoy-like system confirmed all the laboratory results and predictions of high-frequency scattering theory. The proposed system enables the remote, contactless sensing and determination of the principal physical properties of the oil substance spread on the rough water surface on the basis of scattered signal statistics considerations.